GARCH analyses of risk and uncertainty in the theories of the interest rate of Keynes and Kalecki - Hubert Gabrisch (The Vienna Institute for International Economic Studies (wiiw), 2021)
This study attempts to identify uncertainty in the long-term rate of interest based on the controversial interest rate theories of Keynes and Kalecki. While Keynes stated that the future of the rate of interest is uncertain because it is numerically incalculable, Kalecki was convinced that it could be predicted. The theories are empirically tested using a reduced-form GARCH-in-mean model assigned to six globally leading financial markets. The obtained results support Keynes's theory - the long-term rate of interest is a nonergodic financial phenomenon. Analyses of the relation between the interest rate and macroeconomic variables without interest uncertainty are thus seriously incomplete.
Keywords: B26; C58; E43; E47; 330; uncertainty; interest rate; Keynes; Kalecki; GARCH